Effectiveness of diet and physical activity interventions among Chinese-origin populations living in high income countries: a systematic review - Jeannette M. Beasley; Janelle M. Wagnild; Tessa M. Pollard; Timothy R. Roberts; Nasima Ahkter (BMC, 2020)
Abstract Background This review examines the effectiveness of diet and physical activity interventions to reduce cardiometabolic risk among Chinese immigrants and their descendants living in high income countries. The objective of this review is to provide information to help build future interventions aimed at improving diet and increasing physical activity levels among Chinese immigrants. Methods Outcomes included BMI, weight, waist circumference (WC), waist-hip ratio (WHR), cholesterol (LDL, HDL), systolic and diastolic blood pressure (SBP, DBP), hemoglobin A1c (HgbA1c), fasting blood glucose (FBG), and HOMA-IR. Six databases were systematically searched from database inception to date of search (February 2020). Meta-analyses used random effect models to estimate pooled effects of outcomes with 95% confidence intervals. The outcomes assessed were changes in mean outcomes (post-intervention versus baseline) among the intervention group versus control groups. Results Twenty-one articles were included for synthesis, and eight of these were included in the meta-analysis. Among children/adolescents, there were no significant effects of intervention for any of the outcomes having sufficient data for meta-analysis (BMI, WHR, SBP, and DBP). Among adults, the pooled effect including three studies showed significant changes in BMI (effect size = − 1.14 kg/m2; (95% CI: − 2.06, − 0.21), I2 = 31%). There were also significant effects of intervention among adults in terms of changes in SBP and DBP, as the pooled effect across three studies was − 6.08 mmHg (95% CI − 9.42, − 2.73), I2 = 0% and − 3.81 mmHg (95% CI: − 6.34, − 1.28), I2 = 0%, respectively. Among adults there were no other significant effects among the meta-analyses conducted (weight, WC, LDL, HgbA1c, and FBG). Conclusions This review is the first to summarize the effectiveness of diet and physical activity interventions specifically designed for Chinese immigrants living in high income countries. There were clinically meaningful changes in BMI and blood pressure among adults, but evidence was weak for other cardiometabolic outcomes (weight, WC, LDL, HgbA1c, and FBG), and among children, there was no evidence of effect for any cardiometabolic outcomes. Given our mixed findings, more work is needed to support the design of successful interventions, particularly those targeting children and their families. Trial registration The systematic review protocol was registered in PROSPERO on December 17, 2018, the international prospective register of systematic reviews (registration number: CRD42018117842 ).